Application of an intermediate concentration of cyclophosphamide does not specifically deplete regulatory T cells in a mouse experimental model - Radulović, Nataša; Pilipović, Ivan; Stojanović, Ivana (Archives of Biological Sciences, 2023)
Paper description: Cyclophosphamide (100 mg/kg), applied once intraperitoneally to C57BL/6 mice, does not alter proportions or absolute counts of CD4+ cells or CD4+ CD25+ Foxp3+ regulatory T cells (Tregs) in the blood. Cyclophosphamide (100 mg/kg), applied two times 5 days apart, decreased to the same extent the absolute numbers of CD4+ and Tregs. Decreased Treg counts in peripheral blood after cyclophosphamide treatment mirrored the diminished splenic Treg number. Two-dose application of cyclophosphamide does not specifically affect the Treg population in peripheral blood or the spleen and cannot be used as a model for in vivo Treg depletion. Abstract: Cyclophosphamide (CP) is a cytostatic, widely used to treat different carcinomas and autoimmune diseases. It is commonly used in experimental designs modeling immunosuppression in laboratory animals, with different approaches for CP treatment but without a consensus on the dose, timing, and route of administration. We aimed to establish if treatment with CP in C57BL/6 mice depletes regulatory T cells (Tregs). Tregs are a crucial component of the immune system that helps maintain immune tolerance and prevent excessive immune reactions. They are significant in autoimmune diseases, allergies, and immune-related therapies. CP was applied intraperitoneally (i.p.) twice in a 5-day interval in doses of 100 mg/kg. Monitoring of Treg prevalence in peripheral blood after each treatment and in the spleen after the second treatment with CP revealed a drop in the number of Tregs after two doses of CP because of the decreased number of total lymphocytes but not as a specific response of the Tregs. The prevalence of Tregs in peripheral blood after CP treatment mirrored the change in Treg number in the spleen. CP treatment induced a decrease in the number of CD3+ cells in the spleen while increasing their proportion, indicating that CP affected the B lymphocyte population rather than T cells. Our results suggest that CP treatment cannot be used as a specific Treg-depleting agent in the C57BL/6 animal model.